AÇÃO DO LÚPULO EM PACIENTES QUE FAZEM USO DE MEDICAMENTOS PSICOTRÓPICOS (REMUNOM, 2024)
This study explores the interaction of hops (Humulus lupulus) with psychotropic medications, highlighting their potential therapeutic benefits and associated risks. Hops, known for their sedative and anxiolytic properties due to compounds such as alpha acids and 8-prenylnaringenin, can be used to treat anxiety and insomnia disorders. However, when combined with psychotropic medications like antidepressants and anxiolytics, there is a potential to potentiate sedative effects, increasing the risk of excessive sedation and cognitive impairment. Additionally, hops can influence the pharmacokinetics of medications by altering their absorption and metabolism through the cytochrome P450 system. This study underscores the need for rigorous clinical monitoring when considering the combination of hops and psychotropic medications, aiming to maximize therapeutic benefits while minimizing risks to patient health.